2016
DOI: 10.1002/etc.3541
|View full text |Cite
|
Sign up to set email alerts
|

Multigenerational effects of carbendazim in Daphnia magna

Abstract: Carbendazim is a fungicide largely used in agriculture as a plant protection product. As a result of agricultural runoffs, drainage, and leaching, it reaches surface waters at concentrations possibly hazardous to aquatic communities. Because of potential and continuous release of carbendazim to aquatic systems, long-term exposure to aquatic organisms should be addressed. To fill the knowledge gap, the present study evaluated the responses of multiple generations of Daphnia magna (clone K6) to an environmentall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 59 publications
2
8
0
Order By: Relevance
“…In the study of Palanikumar et al (), the milkfish Chanos chanos was exposed to carbendazim and chlorpyrifos, and a possible relationship between DNA damage and fluctuation in antioxidant enzyme responses was found. Silva et al () also found an increase in DNA damage in D. magna from F0 to F12 using an approach similar to ours, with daphnids exposed to carbendazim in a multigenerational experiment, but a straight relationship between DNA damage and antioxidant enzymes could not be established.…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…In the study of Palanikumar et al (), the milkfish Chanos chanos was exposed to carbendazim and chlorpyrifos, and a possible relationship between DNA damage and fluctuation in antioxidant enzyme responses was found. Silva et al () also found an increase in DNA damage in D. magna from F0 to F12 using an approach similar to ours, with daphnids exposed to carbendazim in a multigenerational experiment, but a straight relationship between DNA damage and antioxidant enzymes could not be established.…”
Section: Resultssupporting
confidence: 70%
“…During the multigenerational experiment, an isoclonal population of D. magna was exposed to 5 μg/L of carbendazim throughout 12 generations, with the intention of looking forward and testing the effects over a large temporal time scale. The choice of 12 generations allows a comparison with previous results (Silva et al ), and also takes account of the fact that this fungicide may be present for several months in the field because it is applied on different agricultural crops and at different times during the year (European Commission ). Simultaneously, a second isoclonal population of daphnids was maintained in clean medium and used as control.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…3). Similarly, in previous studies, higher algal consumption in daphnids continuously exposed to lead or fungicides (carbendazim) over several generations has been observed (Araujo et al 2019;Silva et al 2017;Skjolding et al 2014), suggesting that increased food consumption accelerates gut clearance and helps detoxi cation. Thus, our ndings provide evidence that chemical-tolerant clones consume more energy to eliminate pollutants from their body.…”
Section: Discussionsupporting
confidence: 57%
“…This exposure setup can underestimate the adverse effects of chemicals as it excludes exposures during critical stages of development. As a result there is a recent shift in the academic community towards conducting multi-generational exposures for Daphnia , covering exposures during critical stages of development (Giraudo et al 2017 ; Jeong et al 2015 ; Silva et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%